The Effect of Learning Entrepreneurship Courses on PWD Students with Learning Difficulties in a Community College as a Motivator to Venture into Business - Rodziah Binti Ibrahim; Norazlin Binti Adan; Fazlilawati Binti Fadzil (Department of Special Education, 2022)
The involvement of PWD students with learning difficulties in the field of entrepreneurship should be encouraged, starting from the educational institution level. Interest in entrepreneurship needs to be nurtured early during their admission to the learning institution, together with support from the Entrepreneurship Training Unit of the institution. It should also be instilled within the programs by offering them courses that are related to entrepreneurship to train and attract their interest in getting to know more about entrepreneurship while studying at the institution. The government's initiative has been implemented through the Ministry of Higher Education (MOHE) by encouraging the development of curriculum and entrepreneurship courses in higher learning institutions. This initiative aims to provide exposure, awareness, skills, and knowledge related to entrepreneurship, cultivate entrepreneurship in students, and subsequently produce graduates who venture into business as a future career. According to the Progress Report of the Plan of Action for People with Disabilities (PWD) 2016–2022, the number of PWD trainees participating in the Community-Based Rehabilitation (CBR) programs is still unsatisfactory due to the different levels of their disabilities. Therefore, it is recommended that different types of skills and entrepreneurship training be offered to PWD students with learning difficulties based on their abilities. In addition, the PWD policy that was formed strongly encourages them to get involved in entrepreneurship, which also prioritises equality rights that have opened up opportunities for PWD to get involved in the business. However, in general, the policy formed is not specified according to their PWD category. Therefore, according to their ability, Selayang Community College has provided systematic entrepreneurship courses in the Culinary Basic Certificate Programme for PWD students with learning difficulties. This study was conducted to examine the effect of entrepreneurship courses taught as a motivator for them to venture into business as their source of income. PWD students with learning difficulties taking the entrepreneurship courses at Selayang Community College were interviewed using a set of interview questions that had been developed. The recorded interview data were then categorised and translated into word form. The main factor based on the results of the interview data is the effect of learning entrepreneurship courses as a motivator for them to venture into business. Most respondents are interested in venturing into business and becoming entrepreneurs, continuing the legacy of the family business, and seeking experience working with other entrepreneurs (20). While other respondents have not yet decided to venture into business, 83 percent of the survey respondents had a high interest in getting involved in the business after their graduation.